National identity, popular culture and everyday life - Edensor, Tim, 1957- (Berg Publishers, 2002)
The Millennium Dome, Braveheart and Rolls Royce cars. How do cultural icons reproduce and transform a sense of national identity? How does national identity vary across time and space, how is it contested, and what has been the impact of globalizatio n upon national identity and culture? This book examines how national identity is represented, performed, spatialized and materialized through popular culture and in everyday life. National identity is revealed to be inherent in the things we of ten take for granted - from landscapes and eating habits, to tourism, cinema and music. Our specific.